Determination of Blood Flow Characteristics in Eye Vessels in Video Sequence - Chen, Chaoxiang; Ye, Shiping; Chen, Huafeng; Nedzvedz, Alexander; Ablameyko, Sergey; Nedzvedz, Olga (Informatica, 2019)
Accurately measuring blood flow in eye is an important challenge, as blood flow reflects the health of eye and is disrupted in many diseases. Existing techniques for measuring blood flow are limited due to the complex assumptions and calculations required. Digital image and video processing techniques started to be used for eye vessels analysis and evaluation during last decades. In this paper, we propose a method for determining the characteristics of blood flow in the vessels of eye conjunctiva, such as linear and volumetric blood speed, and topological characteristics of vascular net. The method first analyses image frame by frame sequentially and then builds integral optical flow for video sequence. Dynamic characteristics of eye vessels are introduced and calculated. These characteristics make it possible to determine changes in blood flow in eye vessels. We show the efficiency of our method in real eye vessels scenes.